Biaxial strain induced tunable electronic properties study of ZnO nanoparticles via first-principles density functional theory - Soni H.; Singh A.; Mishra A.K. (My University, 2025)
Strain engineering can be used to manipulate electronic and optical properties of ZnO suitable for various applications. In the present work, we have characterized the hydrothermal prepared different wurtzite-ZnO nanoparticles using X-ray diffraction, microscopy and spectroscopy techniques. The lattice parameters of prepared ZnO nanoparticles, obtained from Rietveld refinement of XRD data, have been used for in-depth analysis of the phonon and electronic properties of ZnO. The calculated bandgap Eg using Density functional theory with GGA + U (Generalized Gradient Approximation with Hubbard correction) approach is found to be ∼ 3.48 eV with a strong Zn-3d O-2p hybridization and matches our experimental bandgap value (∼ 3.25 eV). Further, the effect of biaxial strain on the electronic band structure of ZnO has also been studied. A strong non-linear behavior is found in both direct (Γ-Γ) and indirect transitions (Γ-A). Strain application on ZnO may be useful for straintronics and other nano-devices such as NEMS and NOMS. © 2022 Elsevier B.V.